Corporate social reporting in Malaysia: a qualitative approach - Tee, Keng Kok; Roper, Juliet; Kearins, Kate (Faculty of Economics and Management, Universiti Putra Malaysia, 2007)
This paper examines corporate social reporting in Malaysia from the public relations perspective of issues management. Data was derived from case studies of four relatively high impact companies in Malaysia, two owned by multinationals and two Malaysian-owned. An obvious continuum of corporate social reporting practice is apparent with one multinational adopting comprehensive corporate social reporting, the other minimal social reporting within Malaysia (though the parent company reports elsewhere), one Malaysian company engaging in selective disclosure, and the other expressing reservations about this so-called ‘new business’ concept of corporate social responsibility and reporting. Although company representatives interviewed were aware of trends toward increased disclosure, most reflected a desire to shun corporate social responsibility and reporting, in this case, of moral obligations. Our analysis affirms the possibility of the urge to push aside social reporting obligations re-emerging recently as a key aspect of corporate legitimation in Malaysia, as is occurring elsewhere.